HA and M2 sequences alter the replication of 2013–16 H1 live attenuated influenza vaccine infection in human nasal epithelial cell cultures. Issue 32 (30th July 2022) - Canaday, Laura M.; Resnick, Jessica D.; Liu, Hsuan; Powell, Harrison; McCoy, Alyssa M.; Nguyen, Dat; Pekosz, Andrew
Abstract: From 2013 to 2016, the H1N1 component of live, attenuated influenza vaccine (LAIV) performed very poorly in contrast to the inactivated influenza vaccine. We utilized a primary, differentiated human nasal epithelial cell (hNEC) culture system to assess the replication differences between isogenic LAIVs containing the HA segment from either A/Bolivia/559/2013 (rBol), which showed poor vaccine efficacy, and A/Slovenia/2903/2015 (rSlov), which had reasonable vaccine efficacy. There were minimal differences in infectious virus production in Madin-Darby Canine Kidney (MDCK) cells, but the rSlov LAIV showed markedly improved replication in hNEC cultures at both 32 °C and 37 °C, demonstrating that the HA segment alone could impact LAIV replication in physiologically relevant systems. The rSlov-infected hNEC cultures showed stronger production of interferon and proinflammatory chemokines which might also be contributing to the increased overall vaccine effectiveness through enhanced recruitment and activation of immune cells. An M2-S86A mutation had no positive effects on H1 LAIV replication in hNEC cultures, in contrast to the increased infectious virus production seen in an H3 LAIV. No obvious defects in viral RNA packaging were detected, suggesting that HA function, rather than defective particle production, may be driving the differential infectious virus production in hNEC cultures. Overall, we have shown that not all H1 HA segments can be successfully used in LAIV, and this phenotype cannot be fully explained by segment incompatibilities. Physiologically relevant temperatures and primary cell cultures should be used to demonstrate that candidate LAIVs can replicate efficiently, which is a necessary property for effective vaccines.